Dividend Policy and Capital Structure Decision in Family and Non-Family Firms: Evidence From Indonesia - Nadia Azalia Putri; Ana Pratiwi (Cita Konsultindo Research Center, 2022)
Majority firms in Indonesia are family controlled firms. Family control firms have particular agency problem that may affect the company’s performance. As argued, leverage and dividend in the company could be such a tool to counter agency problem. The purpose of this study was to examine the effect of family control on the firms’ capital structure and dividend policy and whether there is difference in capital structure and dividend policy between family and nonfamily firms in Indonesia. This study used a total of 32 listed companies, consisted of 17 family firms and 15 nonfamily firms from period 2018-2021. Multiple linear regression and independent t-test were used to test the hypotheses. Our analysis reveals that family control affect both capital structure and dividend policy. We also found that there is obvious difference in capital structure and dividend policy between family and nonfamily firms. Family firms tend to be indebted than their nonfamily counterparts yet family firms pay less dividend than nonfamily firms